AN INTRODUCTION AND BACKGROUND TO THE BAITFISH RESEARCH PROJECT IN EASTERN INDONESIA - S..J.M. Blaber (Indonesian Fisheries Research Journal, 1998)
Pole-and-line fishing for tuna is a multi-million dollar industry in eastern Indonesia that employs many people, supports several canneries and generates export income.